KEBIJAKAN PEMERINTAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN AGAMA ISLAM (Telaah Peningkatan Kualitas PAI di Kabupaten Pamekasan - Atnawi Atnawi (Universitas Islam Madura, 2018)
The policy of enhancing the management capabilities of educational institutions and implementing the Islamic community development movement (Gerbang Salam) is the jargon of the Pamekasan community, while in terms of the quantity of subject hours, government policies in this case in public schools, ranging from basic education to college level education high. The policy to provide porional and professional religious subjects is also carried out, as well as the policy to enforce the rules that all students who want to enter junior high school must be able to read the Koran well and correctly, in addition, PAI is to maximize the subject matter already stated in the curriculum. The effect is the creation of a civil society atmosphere that aspires to be close to a success. The effect of other government policies in improving the quality of PAI is the increase in personal capabilities (tenagan educators and educational staff) in Pamekasan, then the reduction in the number of juvenile delinquency.